Dual‐Responsive Photocatalytic Polymer Nanogels. (1st July 2019) - Ferguson, Calum T. J.; Huber, Niklas; Landfester, Katharina; Zhang, Kai A. I.
Abstract: Selective activation of photocatalysts under constant light conditions has recently been targeted to produce multi‐responsive systems. However, controlled activation, with easy recovery of the photocatalysts, induced by external stimuli remains a major challenge. Mimicking the responsiveness of biological systems to multiple triggers can offer a promising solution. Herein, we report dual‐responsive polymer photocatalysts in the form of nanogels consisting of a cross‐linked poly‐ N ‐isopropylacrylamide nanogel, copolymerised with a photocatalytically active monomer. The dual‐responsive polymer nanogels undergo a stark decrease in diameter with increasing temperature, which shields the photocatalytic sites, decreasing the activity. Temperature‐dependent photocatalytic formation of NAD+ in water demonstrates the ability to switch photocatalysis on and off. Moreover, the photocatalysed syntheses of several fine chemicals were carried out to demonstrate the utility of the designed material. Abstract : Ansprechender Polymer‐Photokatalysator : Durch die Einbindung photokatalytischer Zentren in ein temperaturabhängiges Polymer‐Nanogel‐Netzwerk entsteht ein dual reaktiver Polymer‐Photokatalysator, mit dem zahlreiche Reaktionen bei spezifischen Temperaturen selektiv katalysiert werden können.